2020
DOI: 10.22547/ber/12.4.5
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Control Laws of South Asian Countries: A Quantitative-Comparative Analysis of Compliance with FCTC and their Effects on Smoking Prevalence

Abstract: Smoking has been the topic of research for long time. Scholars have written on this issue from different dimensions like revenue generation, employment creation, environmental and health hazards. However, it exposes a person to more than 400 carcinogenic chemicals, causing many detrimental diseases like lung cancer, coronary artery disease, heart attack, stroke which kill more than 7 million people annually. Due to high smoking attributable mortality and morbidity; the World Health Organization (hereafter WHO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 20 publications
(16 reference statements)
0
4
0
Order By: Relevance
“…The association between FCTC articles’ implementation and reduced prevalence of tobacco consumption is already reported in literature [ 66 ]. However, the current review found only two FCTC articles (8 & 12) addressed in both empirical and non-empirical records at a satisfactory level.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The association between FCTC articles’ implementation and reduced prevalence of tobacco consumption is already reported in literature [ 66 ]. However, the current review found only two FCTC articles (8 & 12) addressed in both empirical and non-empirical records at a satisfactory level.…”
Section: Discussionmentioning
confidence: 94%
“…The need for coordination between clinical and public policy levels has been highlighted in previous literature from south Asian countries [ 64 , 65 ]. Similarly, a secondary analysis of existing data has shown different countries in South Asia as focusing more on the implementation of specific anti-tobacco policies while lagging in the implementation of others [ 66 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations